Characterization of sp3 carbon produced by plasma deposition on gamma-TiAl alloys - Suparut Narksitipan (2018)
Surfaces of two gamma-TiAl alloys, Ti-47%Al-2%Nb-2%Cr (MJ12) and Ti-47%Al-2%Nb-2%Mn + 0.8%TiB2 (MJ47), were modified by acetylene plasma deposition at -3 kV bias voltage for 0.5-4 h. By using GIXRD and SAED, C (n-diamond), TiC, Al, AlTi, AlTi2, AlTi3, Al0.64Ti0.36 and Al2Ti were detected on both alloys. Additional TiB2 was detected on MJ47. XPS and Raman analyses revealed the presence of sp3 and sp2 carbon deposited on the alloy surfaces with their binding energies of 283.9-284.8 eV for MJ12 and 283.9-285.0 eV for MJ47. Both sp3 and sp2 contents were increased with the increase in the exposure times. The increasing rate of the first was less than that of the second, due to the stress developed in the films. Moiré fringe and crystallographic planes were detected using TEM. Knoop hardness of the deposited alloys, influenced by sp3 carbon, was increased with the increase in the exposure time. Those of MJ12 and MJ47 with 4 h deposition are 1.88 and 1.57 times of the corresponding untreated alloys, respectively. © 2008 Elsevier B.V. All rights reserved.